ANALISIS PRODUKSI PROGRAM SIARAN PILIHAN ANDA DI RADIO FAJRI FM DENGAN MATERI PARENTING ISLAMI - Ivan Wirayumar; Dewi Anggrayni; Retno Triwoelandari (Universitas Pahlawan Tuanku Tambusai, 2022)
The purpose of this study based on the problem statement is to find out the production process of your preferred broadcast program Fajri Fm radio with Islamic parenting material in terms of pre, production, and post-production and to find out fajri FM radio's strategy in maintaining the existence of the broadcast program of your choice. The research method used is a qualitative approach with observation and interview data collection techniques. The author conducts direct research in the field to find out the production process of the program of your choice of Radio Fajri FM. The results of the observations, interviews, and documentation in this study can be concluded that the program of your choice with Islamic parenting material has a live and recorded program format. For the pre-production process, the person in charge of the program and the editor conduct a meeting to determine the theme to be broadcast. In the production process, recording files containing material from speakers are entered into broadcast format. After that, there is post-production, which is the final process that combines all the materials before broadcasting, with various processes such as sound editing, preparing advertisements, checking the sound, so that it is then ready to be broadcast. Keywords: Radio, Fajri FM, Radio Program Production.